Perhitungan Ketebalan Dan Sisa Umur LP Drum HRSG 1.1 PLTGU Muara Karang - Jasmid Edy; Indah Handayasari; M. Nasirudin (JURNAL POWERPLANT, 2016)
In the world of power generation are intimately associated with the boiler and HRSG (heat recovery steam generator), the equipment is functioning as modifiers of water into steam that drives the turbine so that it can turn a generator and produce electricity. HRSG section are instrumental in changing the water into steam is the drum, the drum has a high pressure and temperature so that the equipment must always be inspected every overhaul. Inspection, among others pengkuran drum wall thickness on using Ultrasonic Thickness Testing, this inspection aims to determine the condition of the drum. From the results of these inspections at some point find there is some corrosion on the walls. Then calculated the minimum thickness of the drums and the rest of his life estimates using Standard ASME Boiler and Pressure Vessel Code.